Two new species of Brasineura Silva-Neto & García Aldrete (Psocodea, ‘Psocoptera’, Ptiloneuridae), from Brazil - Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2018)
Two new Brazilian species of Brasineura are described and illustrated, one based on male and female specimens and one based on male specimens only: Brasineura jiboia n.sp. (Bahia: Brazil) and Brasineura spinosa n.sp. (Espírito Santo: Brazil). They differ from the other species in the genus, in which the males are known, by hypandrium and phallosome structures. The first known female Brasineura is described here. The first identification key to males of Brasineura species is presented, as well as a proposal of homology for the structures of the phallosome.